Size-segregated carbonaceous aerosols emission from typical vehicles and potential depositions in the human respiratory system. (September 2020) - Liu, Xi; Kong, Shaofei; Yan, Qin; Liu, Haibiao; Wang, Wei; Chen, Kui; Yin, Yan; Zheng, Huang; Wu, Jian; Qin, Si; Liu, Jinhong; Feng, Yunkai; et al.
Abstract: Particles emitted from five typical types of vehicles (including light-duty gasoline vehicles, LDG; heavy-duty gasoline vehicles, HDG; diesel buses, BUS; light-duty diesel vehicles, LDD and heavy-duty diesel vehicles, HDD) were collected with a dilution sampling system and an electrical low-pressure impactor (ELPI+, with particle sizes covering fourteen stages from 6 nm to 10 μm) on dynamometer benches. The mass concentrations and emission factors (EF) for organic carbon (OC) and elemental carbon (EC) were obtained with a DRI Model 2001 thermal/optical carbon analyzer. A respiratory deposition model was used to calculate the deposition fluxes of size-segregated carbonaceous aerosols in human respiratory system. Results indicated that the OC produced from LDG mainly existed in the size range of 2.5–10 μm, while EC from HDG enriched in 0.94–2.5 μm. For diesel vehicles, both OC and EC concentrations peaked at 0.094–0.25 μm. The OC/EC ratios for PM2.5 varied from different types of vehicles, from 0.61 to 8.35. The primary emissions from LDD and HDD exhibited high OC/EC ratios (>3), suggesting that using OC/EC higher than 2 to indicate the formation of secondary organic aerosol (SOA) was not universal. The emission factors for OC and EC of LDG (HDG) in PM10 were 1.78 (3.14) mg km −1 and 0.88 (4.32) mg km −1, respectively. The OC2 and OC3 were the main section (over 60%) of OC emitted from all the five types of vehicles. EC1 was the most abundant EC fraction of LDG (76.9%), while EC2 dominated for other types of vehicles (more than 62%). About 60% of the OC in ultrafine particles could be deposited in the alveoli. Diesel EC mainly could be deposited in the alveolar region. It is necessary to control the emission of ultrafine particles and diesel EC. Graphical abstract: Image 1 Highlights: OC and EC emitted from diesel vehicles had smaller peak sizes than gasoline vehicles. Using OC/EC higher than 2 to indicate the formation of SOA was not universal. Fourteen size-divided EFOC and EFEC of HDG and LDG were obtained. Carbonaceous aerosols in ultrafine particles and diesel EC were more harmful. Abstract : Emission characteristics, emission factors of size-segregated carbonaceous aerosols from five typical vehicles and their potential deposition fluxes in the respiratory system were demonstrated.